2008
DOI: 10.3324/haematol.13290
|View full text |Cite
|
Sign up to set email alerts
|

Consensus conference on the management of tumor lysis syndrome

Abstract: Tumor lysis syndrome is a potentially life threatening complication of massive cellular lysis in cancers. Identification of high-risk patients and early recognition of the syndrome is crucial in the institution of appropriate treatments. Drugs that act on the metabolic pathway of uric acid to allantoin, like allopurinol or rasburicase, are effective for prophylaxis and treatment of tumor lysis syndrome. Sound recommendations should regulate diagnosis and drug application in the clinical setting. The current ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 61 publications
(71 reference statements)
4
96
0
3
Order By: Relevance
“…The most recent expert TLS guidelines list both ALL and AML with concomitant HL as high-risk for the development of TLS and recommend prophylactic use of rasburicase in addition to aggressive hydration to prevent hyperuricemia (Cairo et al 2010 ). These recommendations concurred with the Italian consensus guidelines for ALL, although in the Italian opinion TLS was rare in AML even with HL and therefore should not be considered high-risk (Tosi et al 2008 ). Cairo et al ( 2010 ) recommend one dose of rasburicase at a dose of 0.1-0.2 mg/kg prior to the initiation of therapy, while Tosi et al ( 2008 ) recommend continuing daily therapy at a dose of 0.2 mg/kg/day for 3-5 days.…”
Section: Management Of Tumor Lysis Syndromesupporting
confidence: 48%
See 2 more Smart Citations
“…The most recent expert TLS guidelines list both ALL and AML with concomitant HL as high-risk for the development of TLS and recommend prophylactic use of rasburicase in addition to aggressive hydration to prevent hyperuricemia (Cairo et al 2010 ). These recommendations concurred with the Italian consensus guidelines for ALL, although in the Italian opinion TLS was rare in AML even with HL and therefore should not be considered high-risk (Tosi et al 2008 ). Cairo et al ( 2010 ) recommend one dose of rasburicase at a dose of 0.1-0.2 mg/kg prior to the initiation of therapy, while Tosi et al ( 2008 ) recommend continuing daily therapy at a dose of 0.2 mg/kg/day for 3-5 days.…”
Section: Management Of Tumor Lysis Syndromesupporting
confidence: 48%
“…These recommendations concurred with the Italian consensus guidelines for ALL, although in the Italian opinion TLS was rare in AML even with HL and therefore should not be considered high-risk (Tosi et al 2008 ). Cairo et al ( 2010 ) recommend one dose of rasburicase at a dose of 0.1-0.2 mg/kg prior to the initiation of therapy, while Tosi et al ( 2008 ) recommend continuing daily therapy at a dose of 0.2 mg/kg/day for 3-5 days. Additionally, the concomitant use of allopurinol (due to the very rarely reported precipitation of uric acid precursor xanthine) and alkalinization (due to potential risk of calcium phosphate precipitation) are not recommended (Coiffi er et al 2008 ;Tosi et al 2008 ;Howard et al 2011 ;Vaitkevičienė et al 2013 ).…”
Section: Management Of Tumor Lysis Syndromesupporting
confidence: 48%
See 1 more Smart Citation
“…These can lead to renal failure, cardiac arrhythmias and death if uncorrected [3]. Those most at risk of developing the condition have malignancies with a large tumour burden, high proliferation rates, or a high sensitivity to chemotherapy agents, and it is most often encountered with the haematological malignancies such as Burkitt's lymphoma and acute lymphoblastic leukaemia [4]. However, even in these patients its incidence is low; one retrospective study of 102 patients found clinically significant tumour lysis syndrome in only 6% of the study population [5].…”
Section: Discussionmentioning
confidence: 99%
“…Increased urine flow in the setting of volume expansion decreases both the calcium-phosphate product in the urine as well as the urine concentration of uric acid, potentially reducing obstructive crystal formation. Current consensus statements suggest fluid intake targets of 3 L/d using intravenous or oral therapy before the start of chemotherapy, provided pre-existing volume overload or oliguric AKI is not present (48).…”
Section: Volume Expansionmentioning
confidence: 99%